2005
DOI: 10.1097/01.fjc.0000179435.26373.81
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Susceptibility to Epinephrine-Induced Arrhythmias

Abstract: Gender differences in incidence of cardiac arrhythmias have been documented. It is generally believed that cardiac pathology provides an arrhythmogenic substrate but that a trigger such as sympathetic nervous system activation is required to initiate arrhythmias. This study was done to determine whether there is a sex difference in susceptibility to epinephrine-induced arrhythmias in healthy rats without preexisting pathology and to determine whether gonadal hormones play a role in development of arrhythmias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Interestingly, OVX has been shown to promote the spontaneous release of SR Ca 2+ [39]. This may explain previous observations that OVX increases arrhythmias in myocardial ischemia and during adrenergic stimulation [24, 107] and could, in part, explain the increase in risk for arrhythmias in post-menopausal women [82]. Taken together, these results suggest that oestrogen suppresses SR Ca 2+ release, limits SR Ca 2+ content and inhibits the spontaneous release of SR Ca 2+ .…”
Section: The Impact Of Sex Steroid Hormones On Cardiac Ec Coupling Mementioning
confidence: 73%
“…Interestingly, OVX has been shown to promote the spontaneous release of SR Ca 2+ [39]. This may explain previous observations that OVX increases arrhythmias in myocardial ischemia and during adrenergic stimulation [24, 107] and could, in part, explain the increase in risk for arrhythmias in post-menopausal women [82]. Taken together, these results suggest that oestrogen suppresses SR Ca 2+ release, limits SR Ca 2+ content and inhibits the spontaneous release of SR Ca 2+ .…”
Section: The Impact Of Sex Steroid Hormones On Cardiac Ec Coupling Mementioning
confidence: 73%
“…Females were also found to have lower sympathetic activation in nonischemic CHF compared to males, whereas males demonstrated greater decline in the inotropic and chronotropic responses to β‐adrenergic stimulation with age in comparison to females (Turner et al, 1999). The susceptibility of animals to catecholamine‐induced arrhythmias was also dependent upon sex (Teplitz et al, 2005). Thus, it appears that responses of heart function to β‐AR stimulation under some conditions may be sex‐dependent, but the mechanisms underlying such differences in male and females are poorly understood.…”
mentioning
confidence: 99%
“…For example, Du and colleagues (14), in the in situ perfused rat heart model with chronic infarction and failure, documented that ventricular arrhythmias, triggered by sympathetic activation, were less frequent in female than in male rats. Similarly, Teplitz and colleagues (46), in the pentobarbital sodium-anesthetized rat, reported that male rat hearts are more susceptible than female hearts to epinephrine-induced arrhythmias and more than twice as many male rats died following epinephrine treatment compared with females. Furthermore, ovariectomy increased the susceptibility to epinephrine-induced arrhythmias, whereas castration had a minimal effect in males.…”
mentioning
confidence: 88%